CLONING AND EXPRESSION OF CATECHOL 2, 3 DIOXYGENASE AND CYCLODEXTRIN GLUCANOTRANSFERASE GENE IN E.COLI AND ITS ROLE IN BIODEGRADATION: Life Science-Environmental sciences - SIVARAMAN C; GANGULY, ANASUYA; MUTNURI, SRIKANTH (International Journal of Life Science and Pharma Research, 2012)
Hydrocarbons are the organic contaminants that enter the environment through natural and anthropogenic processes. Microbial degradation of hydrocarbons is considered as cost effective treatment option. The mass transfer between hydrocarbons to catabolic microflora is highly influenced by its lower aqueous solubility that limits the biodegradation rates. Cyclodextrins with its interior hydrophobic cavity can increase the bioavailability of the hydrophobic compounds. To enhance the biodegradation of hydrocarbons, a catabolic gene (catechol 2, 3 dioxygenase) that is responsible for initial attack on hydrocarbons and cyclodextrin glucanotransferase gene that is responsible for converting starch into cyclodextrins were expressed together in E.coli. The recombinant E.coli was tested for its enhanced degradation in the presence of naphthalene in the presence of starch. At 96 hours enhanced degradation of naphthalene was found in the samples with recombinant E.coli and starch (35.42% + 3.42) when compared with biotic control i.e. samples with recombinant E.coli (62.08% + 1.56).Thus the strategy used in the present study enhances the bioavailability of naphthalene which in turn results in enhanced biodegradation